Research on the application of impedance control in flexible grasp of picking robot. (April 2023) - Zhuang, Min; Li, Ge; Ding, Kexin; Xu, Guansheng
Aiming at the damage of fruit picking robot during the picking process, an impedance control method of picking robot with parameter self-tuning is proposed. The rheological properties of fruit during picking by manipulator were studied by Burger's viscoelasticity theory, and the variation characteristics of fruit deformation during picking, as well as the changing law between fruit contact force and deformation were obtained. On this basis, the impedance control system model of the picking manipulator is established, and the impedance controller is designed. Finally, by constructing the self-correcting change function of impedance parameters, the influence of different impedance parameters on the change of the contact force is studied, and then the control system is improved and designed. The simulation and experimental results show that the established impedance control system model can effectively realize the non-destructive grasping of fruit, and has high grasping accuracy. The expected grasping force is smoother, the overshoot of the contact force is greatly reduced, and the adjustment time is also shortened, which indicates that the control method proposed in this paper has certain application value in the control of picking robots.